Fluoride Alters Klk4 Expression in Maturation Ameloblasts through Androgen and Progesterone Receptor Signaling - Le, Michael H.; Nakano, Yukiko; Abduweli Uyghurturk, Dawud; Zhu, Li; Den Besten, Pamela K. (Frontiers in Physiology, 2017)
Fluorosed maturation stage enamel is hypomineralized in part due to a delay in the removal of matrix proteins to inhibit final crystal growth. The delay in protein removal is likely related to reduced expression of kallikrein related peptidase 4 (KLK4), resulting in a reduced matrix proteinase activity that found in fluorosed enamel. Klk4 transcription is known to be regulated in other cell types by androgen receptor (AR) and progesterone receptors (PR). In this study, we determined the possible role of fluoride in down-regulation of KLK4 expression through changes in AR and PR. Immunohistochemical localization showed that both AR and PR nuclear translocation was suppressed in fluoride exposed mice. However, when AR signaling was silenced in mouse ameloblast-lineage cells (ALCs), expression of both Pgr and Klk4 were increased. Similar to the effect from AR silencing, fluoride also upregulated Pgr in ALCs, but downregulated Klk4. This finding suggests that though suppression of AR transactivation by fluoride increases Prg expression, inhibition of PR transactivation by fluoride has a much greater effect, ultimately resulting in downregulation of Klk4 expression. These findings indicate that in ameloblasts, PR has a dominant role in regulating Klk4 expression. We found that when AR was retained in the cytoplasm in the presence of fluoride, that co-localized with heat shock protein 90 (HSP90), a well-known chaperone for steroid hormone receptors. HSP90 also known to regulate TGF-β signaling. Consistent with the effect of fluoride on AR and HSP90, we found evidence of reduced TGF-β signaling activity in fluorosed ameloblasts as reduced immunolocalization of TGFB1 and TGFBR-2 and a significant increase in Cyclin D1 mRNA expression, which also possibly contributes to the reduced AR signaling activity. In vitro, when serum was removed from the media, aluminum was required for fluoride to inhibit the dissociation of HSP90 from AR. In conclusion, fluoride related downregulation of Klk4 is associated with reduced nuclear translocation of AR and PR, and also reduced TGF-β signaling activity, all of which are regulated by HSP90. We suggest that a common mechanism by which fluoride affects AR, PR, and TGF-β signaling is through inhibiting ATP-dependent conformational cycling of HSP90.